P115 Low dose radiation has a positive impact on bone metabolism in an experimental model of inflammatory arthritis. (21st February 2018) - Deloch, L; Rückert, M; Hueber, AJ; Herrmann, M; Fietkau, R; Frey, B; Gaipl, US
Abstract : Introduction: Rheumatoid arthritis (RA) is, next to inflammation and infiltration of activated immune cells into the synovial joint, characterised by a progressive destruction of cartilage and bone. Although today's treatment options are very effective for many patients, not all of them respond properly or have to reduce medications due to adverse effects. In these patients it is crucial to slow down bone loss and inflammation in a timely manner to prevent further damage. Here, low-dose radiotherapy (LD-RT) could be an option, as it has been shown to ameliorate inflammation and to reduce pain. Using the human TNFα transgenic (h TNFα tg) mouse model as an experimental model of inflammatory arthritis, we revealed that locally applied LD-RT attenuates inflammation in the joints. Objectives: As little is known about the impact of LD-RT on bone metabolism, we thus focused on the effects of LD-RT on bone homeostasis. Methods: Bone marrow-derived osteoclasts (OC) of h TNFα tg mice were differentiated using M-CSF and RANK-L and seeded either on plastic or bone slices prior to irradiation to investigate their numbers and function. Osteoblasts (OB) were differentiated from mouse calvariae, irradiated and analysed regarding their differentiation and function using alizarin red stain and qPCR. Hind legs of h TNFα tg mice were locally irradiated with 0.5 Gy of X-rays and consecutively analysed using histomorphological methods and µCT. Results: Treatment of OC with LD-RT (0.5–2 Gy) lead to decreased differentiation and function, while OB showed increased mineralization after irradiation with 0.5 Gy. Further, no significant increase of Acp5 and catk at 0.5 Gy was found in OC while OB showed a dose-dependent decrease in RANK-L and increase in OPG expression. Also, OPG secretion by OB was enhanced at 0.5 Gy and 1 Gy. Histomorphometric analyses showed a decrease of erosive areas and OC numbers in the paws of irradiated animals, a finding that was confirmed in µCT images. Conclusions: We conclude that LD-RT is not only a valuable tool for reduction of inflammation, but also has beneficial effects in restoring a balanced bone homeostasis through increased OB mineralization and decreased OC function. In the future, placebo controlled studies are desirable in order to investigate the effects of LD-RT with focus on osteoimmunology in RA in the clinic. Acknowledgements: Supported by the German Federal Ministry of Education and Research (GREWIS, 02NUK017G and GREWIS-alpha, 02NUK050E Disclosure of interest: None declared